Freedom, choice, and the sense of agency - Barlas, Zeynep; Obhi, Sukhvinder (Frontiers in Human Neuroscience, 2013)
The sense of agency is an intriguing aspect of human consciousness and is commonly defined as the sense that one is the author of their own actions and their consequences. In the current study, we varied the number of action alternatives (one, three, seven) that participants could select from and determined the effects on intentional binding which is believed to index the low-level sense of agency. Participants made self-paced button presses while viewing a conventional Libet clock and reported the perceived onset time of either the button presses or consequent auditory tones. We found that the binding effect was strongest when participants had the maximum number of alternatives, intermediate when they had medium level of action choice and lowest when they had no choice. We interpret our results in relation to the potential link between agency and the freedom to choose one’s actions.